Consumer price indexes and inflation in Suriname since 1954 (an account) (General Bureau of Statistics ParamariboSR, 2002)
Looks at three household budget surveys conducted in Suriname and compares them looking at characteristics such as: number of households or families; response percentage; duration of the survey; name of the index; calculation weighting schedule; and, number of items per major group using the 1968/1969 schedule. Examines annual inflation and highlights Suriname's new consumer price index using a question and answer approach.
Keywords: PRICE INDEXES